Partial Status Epilepticus after Electroconvulsive Therapy and Medical Treatment with Bupropion - Dersch, R.; Zwernemann, S.; Voderholzer, U. (Pharmacopsychiatry, 2011)
Electroconvulsive therapy (ECT) is the most effective treatment for therapy-refractory depression. Usually, prior antidepressant medication will be continued during ECT. However, the seizure threshold may be influenced by psychotropic drugs. We report a patient who received right unilateral ECT under concomitant treatment with bupropion, a selective noradrenaline- and dopamine-reuptake inhibitor. After the fourth session, a focal status epilepticus occurred, which was pharmacoresistant for the duration of 12 days. We assume that the induction of a status may be facilitated by a lowering of the seizure threshold due to bupropion. An evaluation of drug therapy and control of EEG before and during ECT are recommended, especially when the drug treatment has an influence on the seizure threshold.
Keywords: electroconvulsive therapy; partial status epilepticus; bupropion; antidepressant treatment